2018
DOI: 10.1177/2473974x18764862
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method of Endoscopic Intrasphenoidal Vidian Neurectomy

Abstract: ObjectiveTo develop an easy surgical approach to facilitate clinical management.Study DesignA novel transnasal endoscopic 3-step surgical method for vidian neurectomy was designed and tried in 91 cases with a mild-to-severe degree of allergic and nonallergic rhinitis refractory to routine medical therapy.SettingEndoscopic vidian neurectomy requires accurate localization of the vidian canal. However, it is not easy to localize during surgery because of its deep location and the complex anatomy of the pterygopal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The endoscope for middle ear surgery has been a highly contentious subject with the introduction of high-quality narrow-diameter endoscopes, ultra-high-definition cameras and screens, and cold light sources [ 5 ]. In contrast to the microscope, the endoscope has a cone-shaped source of illumination, which ensures optimal visualization and allows a wider field of view of the surgical area [ 6 ]. Endoscopic ear surgery permits a wide-angle view throughout the external ear canal, including magnification of the middle ear structures and direct visualization of hidden areas [ 7 ], such as the sinus tympani, hypotympanum, posterior part of the mesotympanum, and epitympanum [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The endoscope for middle ear surgery has been a highly contentious subject with the introduction of high-quality narrow-diameter endoscopes, ultra-high-definition cameras and screens, and cold light sources [ 5 ]. In contrast to the microscope, the endoscope has a cone-shaped source of illumination, which ensures optimal visualization and allows a wider field of view of the surgical area [ 6 ]. Endoscopic ear surgery permits a wide-angle view throughout the external ear canal, including magnification of the middle ear structures and direct visualization of hidden areas [ 7 ], such as the sinus tympani, hypotympanum, posterior part of the mesotympanum, and epitympanum [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] We and others demonstrated that vidian neurectomy under nasal endoscopy improved nasal allergic symptoms and quality of life in patients with AR. 16,17 Our previous animal experiments demonstrated that ipratropium bromide, a nonspecific cholinergic nerve receptor antagonist, alleviated nasal symptoms and Th2 cytokines in the nasal mucosa in AR. 8,9 However, the role of m3 in AR remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of computed tomography examination technology and endoscopic technology, the localization of the vidian canal has become more accurate, and the vision of endoscopic vidian neurectomy (EVN) clearer [10]. EVN for AR has been found to have good clinical effects [11, 12]. However, the pathophysiological basis of the effect of EVN on AR is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%